Monitoring of central retinal artery and vein with color doppler ultrasound during heart surgery as an alternative to transcranial doppler ultrasonography: A case report. Issue 2 (22nd April 2013) - Venturini, Massimo; Zambon, Massimo; Cristel, Giulia; Agostini, Giulia; Querques, Giulia; Colombo, Michele; Benussi, Stefano; Landoni, Giovanni; Zangrillo, Alberto; Del, Alessandro
ABSTRACT Cardiac surgery can have severe neurologic complications. The noninvasive monitoring of intracranial circulation during heart surgery is usually performed with transcranial Doppler ultrasonography. We present the case of a 66‐year‐old man who underwent elective cardiac surgery for aortic valve replacement and coronary artery bypass graft, in whom monitoring was performed by simultaneously assessing blood flow velocity in the central retinal artery and vein. © 2013 Wiley Periodicals, Inc. J Clin Ultrasound42:112–115, 2014